An anti-cracking water-reducing agent suitable for alkali-activated cement and its preparation process and application
By developing a polynaphthalenesulfonic acid silicone derivative anti-cracking water reducing agent, the problem of poor fluidity of alkali-activated cement in high alkali environment and failure of traditional water reducing agents is solved, and the water use reduction in alkali-activated cement is achieved , improve liquidity and reduce cracking risk.
Patent Information
- Application Number
- CN202410559759.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-08
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-05-08
AI Technical Summary
In engineering applications, alkali-activated cement has problems such as large shrinkage, poor fluidity, difficulty in regulation of workability, and failure of traditional water-reducing agents in high alkali environments, which limits its wide application in engineering.
Develop a water-resistant cracking agent, which prepares raw materials including refined naphthalene, formaldehyde solution, bihydroxyl-terminated dimethyl silicone oil, alkali liquid, sodium dodecyl benzene sulfonate, sulfate and water, through specific process steps and reaction conditions, polynaphthalenesulfonic acid silicone derivatives are formed, with high stability and good fluidity regulation effect.
This anti-cracking water reducing agent is stable in a high alkali environment, effectively reducing the amount of water used, improving the fluidity of alkali-activated cement slurry, significantly reducing the shrinkage and cracking of alkali-activated cement after hardening, and reducing the risk of cracking and damage.
Smart Images

Figure CN118459147B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement preparation, and in particular to an anti-cracking water reducing agent suitable for alkali-activated cement and a preparation process and application thereof. Background Art
[0002] At present, it has become a focus to replace Portland cement with alkali-activated cement prepared from industrial wastes such as slag and fly ash. However, there are also many problems. First, the shrinkage of alkali-activated cement is large, about 2 to 4 times that of ordinary silicate cement, which greatly limits the wide application of alkali-activated cement in engineering. Second, the time loss of alkali-activated cement paste is large and the fluidity is poor under low water-cement ratio. However, if the water-cement ratio is too large, the hardening rate of alkali-activated cement paste will be significantly slowed down, increasing the risk of cracking and brittle fracture of the hardened body. Therefore, the workability of alkali-activated cement is not easy to control, which brings great difficulties to construction. Third, traditional admixtures (such as water reducers) used to control the workability of cement-based metamaterials will fail in alkali-activated cement, because such admixtures are difficult to exist stably in the high alkaline environment of alkali-activated cement. The above problems make it difficult for alkali-activated cement to truly replace Portland cement in engineering, resulting in a decrease in the resource utilization rate of industrial wastes such as slag and fly ash. Summary of the invention
[0003] In view of the above problems, the present invention provides an anti-cracking water-reducing agent suitable for alkali-activated cement and its preparation process and application. The anti-cracking water-reducing agent can stably exist in alkali-activated cement in a high-alkali environment, can effectively reduce the amount of water used and improve the fluidity of the alkali-activated cement paste. Specifically, the present invention discloses the technical solution as shown below.
[0004] Firstly, the invention discloses an anti-cracking water reducing agent suitable for alkali-activated cement. The raw materials for preparing the anti-cracking water reducing agent include the following components in parts by weight: 400-500 parts of refined naphthalene, 150-200 parts of formaldehyde solution, 80-100 parts of dihydroxy-terminated dimethyl silicone oil, 100-120 parts of alkali solution, 15-20 parts of sodium dodecylbenzene sulfonate (SDBS), 80-100 parts of sulfate solution and 300-500 parts of water.
[0005] Further, the alkali solution includes at least one of a sodium hydroxide solution, a potassium hydroxide solution, etc. Optionally, the mass fraction of the alkali solution is 30-40%.
[0006] Furthermore, the mass fraction of the formaldehyde solution is 40-55%.
[0007] Further, the sulfate includes at least one of sodium sulfate, potassium sulfate, etc. Optionally, the mass fraction of the sulfate solution is 20-30%.
[0008] Secondly, the present invention discloses a preparation process of an anti-cracking water reducing agent suitable for alkali-activated cement, comprising the following steps:
[0009] (1) The dihydroxy-terminated dimethyl silicone oil and formaldehyde solution are mixed, and then a portion of the sodium dodecylbenzene sulfonate is added. After heating, water is added under stirring. After the reaction, the mixture is cooled to obtain a solution A for standby use.
[0010] (2) After the refined naphthalene is melted, concentrated sulfuric acid is used as a catalyst and a sulfonation reaction is carried out under heating conditions. After completion, water is added to continue the reaction. After completion, the solution is cooled to a set temperature and kept warm to obtain a solution B.
[0011] (3) The sulfate solution, alkali solution and water are mixed and allowed to stand to obtain a solution C for later use.
[0012] (4) sodium dodecylbenzene sulfonate and part of the solution A are added to the solution B, and then reacted under heating conditions. After completion, the remaining solution A is added to continue the reaction. After completion, the solution C is added to adjust the pH of the system to alkaline, and the anti-cracking water-reducing agent is obtained after standing.
[0013] Further, in step (1), the heating temperature is 200-220° C., and the reaction time is 24-48 hours. In this process, the formaldehyde and dihydroxy-terminated dimethyl silicone oil react under the catalytic action of sodium dodecylbenzene sulfonate (as shown in Formula 1), so that the formaldehyde and hydrophobic siloxane undergo polymerization, and the final product reduces the risk of cracking by being hydrophobic, because the introduced hydrophobic group (methyl) final product will be free in free water or adsorbed on cement particles, and the presence of these hydrophobic groups will cause the pore surface tension to decrease when the slurry hardens, thereby reducing the risk of cracking caused by capillary stress.
[0014]
[0015] Furthermore, in step (2), the heating temperature is 160-170° C., and the reaction time is 2-6 hours. The reaction is continued until the acidity reaches 20-25%, and then cooled to 80-90° C. for insulation to obtain the solution B. In this process, the refined naphthalene undergoes a sulfonation reaction as shown in Formula 2 to form naphthalenesulfonic acid, so as to be added to the polymerization reaction of the following Formula 3.
[0016]
[0017] Furthermore, in step (3), the standing time is 24 to 48 hours.
[0018] Furthermore, in step (4), the heating temperature is 160-180°C and the reaction time is 3-6 hours. In this process, the solution A and the solution B react as shown in Formula 3 under the catalytic action of sodium dodecylbenzene sulfonate to obtain a water reducer (polynaphthalenesulfonic acid siloxane derivative) grafted with a hydrophobic group. The sulfate in the solution C can effectively absorb metal ions such as sodium and potassium and OH - Etc., reduce the impact on the sulfonic acid group and reduce the hydrolysis of sulfonates.
[0019] Furthermore, in step (4), the remaining solution A accounts for 40 to 55% of the total solution A. Optionally, the reaction is continued for 4 to 6 hours.
[0020] Furthermore, in step (4), the pH of the system is adjusted to 9-10 to neutralize H + Too high acidity will lead to instability of silanol, affecting the adsorption effect of anti-cracking water-reducing agent molecules, and thus reducing the anti-cracking alkaline water effect.
[0021]
[0022] Furthermore, the sodium dodecylbenzene sulfonate in step (1) accounts for 30-35% of the sodium dodecylbenzene sulfonate in the raw material, and the rest of the sodium dodecylbenzene sulfonate is used in step (4).
[0023] Furthermore, the water in steps (1) and (2) accounts for 25-30% and 40-50% of the water in the raw material respectively, and the remaining water is used in step (3).
[0024] Finally, the present invention discloses the use of the anti-cracking water reducing agent in alkali-activated cement-based concrete materials. Optionally, the amount of the anti-cracking water reducing agent is 1-3% of the alkali-activated cement component.
[0025] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects:
[0026] The anti-cracking water-reducing agent prepared by the present invention has high stability in a highly alkaline environment and will not fail. This is because: the essence of the water-reducing agent is to adsorb on the surface of cement particles to provide electrostatic repulsion, reduce particle friction, reduce the free water content of the package, and improve fluidity. However, the high pH environment of alkali-activated cement will cause the molecular structure of the water-reducing agent to be destroyed into small molecules, which will adsorb Na + OH -The ions (provided by the high pH environment) are adsorbed onto the cement particles, resulting in a decrease in the amount of water-reducing agent molecules adsorbed on the cement particles, a decrease in steric hindrance, and a decrease in the water-reducing effect. The sulfonate contained in the water-reducing agent (as shown in the above formula 3) prepared by the present invention has more adsorption sites for the carboxyl groups than the traditional polycarboxylate water-reducing agent, thereby being able to adsorb more sodium, potassium ions and OH. - And the sulfate contained is a strong electrical group, which can adsorb a large amount of these ions, thereby reducing the Na + OH - The influence of plasma on sulfonic acid groups. Therefore, after the water reducer of the present invention is added to cement, more water reducer molecules can be adsorbed on cement particles, ensuring a good water reduction effect. In addition, the water reducer (polynaphthalenesulfonic acid siloxane derivative) prepared by the present invention contains silanol groups (Si-OH), which are hydrolyzed and dehydrogenated in the alkaline environment of alkali-activated cement to form silicon-oxygen bonds (-Si-OH+OH - →-Si-O-+H2O) can chemically combine with the surface of cement particles (the main chemical structure of the surface of alkali-activated cement particles is: -Si-O-, -Al-O- or -Si-Al-O-), thereby wrapping the cement particles. At this time, the negative charge carried by the sulfonic acid group on the anti-cracking water-reducing agent causes the alkali-activated cement particles to repel each other due to the electrostatic steric effect, further enhancing the steric effect of the cement particles and improving the water-reducing effect. Compared with the traditional water-reducing agent that simply physically adsorbs onto cement particles, the chemical combination method of the present invention will greatly reduce the time loss of cement slurry and greatly improve the fluidity of the slurry formed by alkali-activated cement materials. This is because after the electrostatic steric effect of cement particles is enhanced, the agglomeration of cement particles can be effectively reduced, the free water content in the cement slurry is significantly increased, and the fluidity is prevented from being reduced due to the agglomeration of cement particles.
[0027] At the same time, the anti-cracking water-reducing agent wrapped on the alkali-activated cement particles forms a hydrophobic layer on the surface of the cement particles. As hydration proceeds, the alkali-activated cement-based material slurry gradually hardens and forms micropores in the hardened body, and the groups of the anti-cracking water-reducing agent are also exposed on the inner wall of the micropores or dispersed in the interstitial water. At this time, the methyl side chains of the methylsiloxane of the anti-cracking water-reducing agent form a hydrophobic oil-like phase, so that the inner wall of the micropores also forms a hydrophobic layer, thereby reducing the shrinkage microstress generated by capillary stress in the hardening process of the alkali-activated cement-based material slurry, reducing cracking caused by volume shrinkage, and preventing the degradation of the mechanical properties of the hardened body.
[0028] The above-mentioned anti-cracking water-reducing agent of the present invention not only effectively solves the problem of instability and performance failure of existing water-reducing agents in high-alkali environments, thereby reducing the water consumption of alkali-activated cement while ensuring its good fluidity, but also can significantly reduce the shrinkage cracking of alkali-activated cement after hardening and reduce the risk of cracking and damage. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0030] Figure 1 This is a sample picture of the anti-cracking water-reducing agent prepared in the following Example 1.
[0031] Figure 2 This is a compressive strength test diagram of the alkali-activated cement mortar test block of the following Example 1.
[0032] Figure 3 This is a test diagram of the flexural strength of the alkali-activated cement mortar specimen of Example 1 below.
[0033] Figure 4 The following is a graph showing the plastic shrinkage of the alkali-activated cement mortar of Example 1. DETAILED DESCRIPTION
[0034] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0035] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. Unless otherwise specified, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions.
[0036] In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. The technical solution of the present invention is further described in conjunction with the accompanying drawings and specific embodiments.
[0037] Example 1
[0038] A preparation process of an anti-cracking water-reducing agent suitable for alkali-activated cement comprises the following steps:
[0039] (1) Take the following raw materials in parts by weight: 500 parts of refined naphthalene, 200 parts of 50% formaldehyde solution, 80 parts of dihydroxy-terminated dimethyl silicone oil, 100 parts of 30% sodium hydroxide solution, 18 parts of sodium dodecylbenzene sulfonate, 100 parts of 20% sodium sulfate solution, and 400 parts of water.
[0040] (2) The dihydroxy-terminated dimethyl silicone oil and the formaldehyde aqueous solution were mixed, and then 6 parts of the sodium dodecylbenzene sulfonate were added. The mixture was heated to 200° C. and then 100 parts of the water were added while being stirred (stirring rate: 1200 r / min) for dilution. The mixture was then reacted for 24 hours to obtain a solution A for later use.
[0041] (3) Using concentrated sulfuric acid as a catalyst, the refined naphthalene is added into a sulfonation kettle, melted, and then heated to 165° C. for reaction for 3 h, then 200 parts of water is added under rapid stirring, and the reaction is continued until the acidity of the system reaches 23%, and then cooled to 85° C. and kept warm to obtain solution B.
[0042] (4) The sodium sulfate solution, the sodium hydroxide solution and 100 parts of the water are mixed and stirred evenly, and then allowed to stand for 36 hours to obtain a solution C for standby use.
[0043] (5) Add the solution B, the remaining sodium dodecylbenzene sulfonate and half of the solution A to a reactor, stir evenly and heat to 180° C. for reaction for 3 h, then add the remaining solution A, continue the reaction for 4 h, then add the solution C to adjust the pH of the system to 10, and obtain an anti-cracking water-reducing agent (such as Figure 1 shown).
[0044] Performance Testing
[0045] 1. Take the following raw materials: 450 parts by weight of alkali activated cement, 1350 parts by weight of fine aggregate, 100 parts by weight of alkaline activator, 4.5 parts by weight of the anti-cracking water reducing agent prepared in this embodiment, and 130 parts by weight of mixing water. Among them: the alkaline activator is a mixture of 40% sodium silicate and 10% sodium carbonate solution in a mass ratio of 9:1, and the fine aggregate is standard sand.
[0046] 2. Mix the anti-cracking water-reducing agent, activator and mixing water and stir them quickly and evenly. The resulting liquid is ready for use.
[0047] 3. Add the cement and fine aggregate into a mortar mixer and dry mix for 2 minutes, then continue to stir the liquid for another 2 minutes to obtain alkali-activated cement mortar.
[0048] The various performance indicators of the alkali-activated cement mortar test block prepared in this embodiment were tested: (1) According to GB / T17671-1999 "Test method for strength of cement mortar (ISO method)" and GB / T29417-2012 "Test method for drying shrinkage cracking performance of cement mortar and concrete", the compressive strength of the alkali-activated cement mortar test block (such as Figure 2 As shown), flexural strength (as shown Figure 3(as shown), splitting tensile strength. (2) According to JGJ / T70-2009 "Standard for Test Methods for Basic Properties of Building Mortar", the setting time of the alkali-activated cement mortar specimen was measured using a penetration resistance meter. (3) According to JC / T 603-200 "Test Method for Drying Shrinkage of Cement Mortar", the plastic shrinkage of the alkali-activated cement mortar (as shown) was measured using a non-contact bellows shrinkage deformation measuring instrument and a vertical mortar shrinkage meter. Figure 4 The test results are shown in the following table.
[0049]
[0050] Example 2
[0051] A preparation process of an anti-cracking water-reducing agent suitable for alkali-activated cement comprises the following steps:
[0052] (1) Take the following raw materials in parts by weight: 450 parts of refined naphthalene, 170 parts of 40% formaldehyde solution, 90 parts of dihydroxy-terminated dimethyl silicone oil, 105 parts of 40% sodium hydroxide solution, 15 parts of sodium dodecylbenzene sulfonate, 80 parts of 30% sodium sulfate solution, and 500 parts of water.
[0053] (2) The dihydroxy-terminated dimethyl silicone oil and the formaldehyde aqueous solution were mixed, and then 5 parts of the sodium dodecylbenzene sulfonate were added. After heating to 220° C., 150 parts of the water were added while stirring (stirring rate 1200 r / min) for dilution, and then reacted for 36 hours to obtain solution A for standby use.
[0054] (3) Using concentrated sulfuric acid as a catalyst, the refined naphthalene is added into a sulfonation kettle, melted, and then heated to 160° C. for reaction for 6 hours. Then, 200 parts of water is added under rapid stirring, and the reaction is continued until the acidity of the system reaches 20%. Then, the mixture is cooled to 80° C. and kept warm to obtain solution B.
[0055] (4) The sodium sulfate solution, the sodium hydroxide solution and 150 parts of the water are mixed and stirred evenly, and then allowed to stand for 48 hours to obtain a solution C for standby use.
[0056] (5) Add the solution B, the remaining sodium dodecylbenzene sulfonate and half of the solution A to a reactor, stir evenly and heat to 170° C. to react for 5 hours, then add the remaining solution A, continue to react for 4 hours, and then add the solution C to adjust the pH of the system to 10, thereby obtaining an anti-cracking water-reducing agent.
[0057] The same method as in the above-mentioned Example 1 was used to test various performance indicators of the alkali-activated cement mortar test block prepared in this example. The results are shown in the following table.
[0058]
[0059] Example 3
[0060] A preparation process of an anti-cracking water-reducing agent suitable for alkali-activated cement comprises the following steps:
[0061] (1) Take the following raw materials in parts by weight: 400 parts of refined naphthalene, 150 parts of 55% formaldehyde solution, 100 parts of dihydroxy-terminated dimethyl silicone oil, 120 parts of 35% potassium hydroxide solution, 20 parts of sodium dodecylbenzene sulfonate, 95 parts of 25% potassium sulfate solution, and 300 parts of water.
[0062] (2) The dihydroxy-terminated dimethyl silicone oil and the formaldehyde aqueous solution were mixed, and then 7 parts of the sodium dodecylbenzene sulfonate were added. The mixture was heated to 210° C. and then 100 parts of the water were added while being stirred (stirring rate: 1200 r / min) for dilution. The mixture was then reacted for 48 hours to obtain a solution A for later use.
[0063] (3) Using concentrated sulfuric acid as a catalyst, the refined naphthalene is added into a sulfonation kettle to be melted and then heated to 170° C. for reaction for 2 h, then 200 parts of water is added under rapid stirring, and the reaction is continued until the acidity of the system reaches 25%, and then the solution is cooled to 90° C. and kept warm to obtain solution B.
[0064] (4) The potassium sulfate solution, the sodium hydroxide solution and 100 parts of the water are mixed and stirred evenly, and then allowed to stand for 24 hours to obtain a solution C for standby use.
[0065] (5) Add the solution B, the remaining sodium dodecylbenzene sulfonate and half of the solution A to a reactor, stir evenly and heat to 160° C. to react for 6 hours, then add the remaining solution A, continue to react for 4 hours, and then add the solution C to adjust the pH of the system to 9, thereby obtaining an anti-cracking water-reducing agent.
[0066] The same method as in the above-mentioned Example 1 was used to test various performance indicators of the alkali-activated cement mortar test block prepared in this example. The results are shown in the following table.
[0067]
[0068] Example 4
[0069] A preparation process of an anti-cracking water-reducing agent suitable for alkali-activated cement comprises the following steps:
[0070] (1) Take the following raw materials in parts by weight: 500 parts of refined naphthalene, 200 parts of 50% formaldehyde solution, 80 parts of dihydroxy-terminated dimethyl silicone oil, 100 parts of 30% sodium hydroxide solution, 18 parts of sodium dodecylbenzene sulfonate, 100 parts of 20% sodium sulfate solution, and 400 parts of water.
[0071] (2) The dihydroxy-terminated dimethyl silicone oil and the formaldehyde aqueous solution were mixed, and then 6 parts of the sodium dodecylbenzene sulfonate were added. The mixture was heated to 200° C. and then 100 parts of the water were added while being stirred (stirring rate: 1200 r / min) for dilution. The mixture was then reacted for 24 hours to obtain a solution A for later use.
[0072] (3) The refined naphthalene is added to a sulfonation kettle and melted, and then the temperature is raised to 165° C. for reaction for 3 hours, and then 200 parts of water is added under rapid stirring, and then cooled to 85° C. and kept warm to obtain solution B.
[0073] (4) The sodium sulfate solution, the sodium hydroxide solution and 100 parts of the water are mixed and stirred evenly, and then allowed to stand for 36 hours to obtain a solution C for standby use.
[0074] (5) Add the solution B, the remaining sodium dodecylbenzene sulfonate and half of the solution A to a reactor, stir evenly and heat to 180° C. to react for 3 h, then add the remaining solution A, continue to react for 4 h, then add the solution C to adjust the pH of the system to 10, and obtain an anti-cracking water-reducing agent.
[0075] The same method as in the above-mentioned Example 1 was used to test various performance indicators of the alkali-activated cement mortar test block prepared in this example. The results are shown in the following table.
[0076]
[0077] Example 5
[0078] A preparation process of an anti-cracking water-reducing agent suitable for alkali-activated cement is the same as the above-mentioned embodiment 2, except that the steps of this embodiment are as follows: the solution B, the remaining sodium dodecylbenzene sulfonate and all the solution A are added to a reactor, stirred evenly and heated to 170° C. for reaction for 9 hours, and then the solution C is added to adjust the pH of the system to 10 to obtain the anti-cracking water-reducing agent.
[0079] The same method as in the above-mentioned Example 1 was used to test various performance indicators of the alkali-activated cement mortar test block prepared in this example. The results are shown in the following table.
[0080]
[0081] Example 6
[0082] A preparation process of an anti-cracking water-reducing agent suitable for alkali-activated cement, which is the same as the above-mentioned embodiment 3, except that the raw materials of step (1) of this embodiment do not contain the dihydroxy-terminated dimethyl silicone oil. Therefore, step (2) is: add 7 parts of the sodium dodecylbenzene sulfonate to the formaldehyde aqueous solution, heat to 210°C, add 100 parts of the water while stirring (stirring rate 1200r / min) to dilute, and then react for 48h to obtain solution A.
[0083] The same method as in the above-mentioned Example 1 was used to test various performance indicators of the alkali-activated cement mortar test block prepared in this example. The results are shown in the following table.
[0084]
[0085] Example 7
[0086] A preparation process of an anti-cracking water-reducing agent suitable for alkali-activated cement is the same as that of the above-mentioned embodiment 2, except that the raw material of step (1) of this embodiment does not contain the sodium sulfate solution. Therefore, step (4) is: mixing the sodium hydroxide solution and 150 parts of the water, stirring evenly, and then standing for 48 hours to obtain solution C.
[0087] The same method as in the above-mentioned Example 1 was used to test various performance indicators of the alkali-activated cement mortar test block prepared in this example. The results are shown in the following table.
[0088]
[0089]
[0090] Example 8
[0091] A preparation process of an anti-cracking water reducing agent suitable for alkali-activated cement is the same as the above-mentioned embodiment 3, except that the raw material of step (1) of this embodiment does not contain the formaldehyde solution and is replaced with clean water. Therefore, step (2) is: mixing the dihydroxy-terminated dimethyl silicone oil and clean water, then adding 7 parts of the sodium dodecylbenzene sulfonate, heating to 210°C, and then adding 100 parts of the water to dilute while stirring (stirring rate 1200r / min), and then reacting for 48h to obtain solution A.
[0092] The same method as in the above-mentioned Example 1 was used to test various performance indicators of the alkali-activated cement mortar test block prepared in this example. The results are shown in the following table.
[0093] Example 9
[0094] 1. Take the following raw materials: 450 parts by weight of alkali activated cement, 1350 parts by weight of fine aggregate, 100 parts by weight of alkaline activator, 4.5 parts by weight of traditional polycarboxylic acid alkaline water agent, and 130 parts by weight of mixing water. Among them: the alkaline activator is a mixture of 40% sodium silicate and 10% sodium carbonate solution in a mass ratio of 9:1, and the fine aggregate is standard sand.
[0095] 2. Mix the anti-cracking water-reducing agent, activator and mixing water and stir them quickly to make them uniform. The resulting liquid is ready for use.
[0096] 3. Add the cement and fine aggregate into a mortar mixer and dry mix for 2 minutes, then continue to stir the liquid for another 2 minutes to obtain alkali-activated cement mortar.
[0097] The same method as in the above-mentioned Example 1 was used to test various performance indicators of the alkali-activated cement mortar test block prepared in this example. The results are shown in the following table.
[0098]
[0099]
[0100] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An anti-cracking water reducing agent suitable for alkali-activated cement, characterized in that: The raw materials for preparing the anti-cracking water reducing agent include the following components in parts by weight: 400-500 parts of refined naphthalene, 150-200 parts of formaldehyde solution, 80-100 parts of dihydroxy-terminated dimethyl silicone oil, 100-120 parts of alkali solution, 15-20 parts of sodium dodecylbenzene sulfonate, 80-100 parts of sulfate solution, and 300-500 parts of water; the water reducing agent is prepared by the following steps: (1) mixing the dihydroxy-terminated dimethyl silicone oil with formaldehyde solution, adding part of the sodium dodecylbenzene sulfonate, heating, adding water under stirring, cooling after reaction, obtaining solution A for standby use; (2) After the refined naphthalene is melted, concentrated sulfuric acid is used as a catalyst and a sulfonation reaction is carried out under heating conditions. After the reaction is completed, water is added to continue the reaction. After the reaction is completed, the solution is cooled to a set temperature and kept warm to obtain a solution B; (3) mixing the sulfate solution, alkali solution and water and letting the mixture stand to obtain a solution C for later use; (4) adding sodium dodecylbenzene sulfonate and part of the solution A to the solution B, and then reacting under heating conditions, and after completion, adding the remaining solution A to continue the reaction; after completion, adding the solution C to adjust the pH of the system to alkaline, and after standing to obtain the anti-cracking water-reducing agent; In step (1), the heating temperature is 200-220° C., and the reaction time is 24-48 hours; the sodium dodecylbenzene sulfonate accounts for 30-35% of the sodium dodecylbenzene sulfonate in the raw material, and the remaining sodium dodecylbenzene sulfonate is used in step (4); The water in steps (1) and (2) accounts for 25-30% and 40-50% of the water in the raw material respectively, and the remaining water is used in step (3); In step (2), the heating temperature is 160-170° C., and the sulfonation reaction time is 2-6 hours; the reaction is continued until the acidity reaches 20-25%, and then cooled to 80-90° C. and kept warm to obtain the solution B; In step (3), the standing time is 24 to 48 hours; In step (4), the heating temperature is 160-180° C., and the reaction time under the heating condition is 3-6 hours; the remaining solution A accounts for 40-55% of the total solution A; the continued reaction time is 4-6 hours; and the pH of the system is adjusted to 9-10.
2. The anti-cracking water reducing agent suitable for alkali-activated cement according to claim 1, characterized in that: The alkali solution includes at least one of a sodium hydroxide solution and a potassium hydroxide solution.
3. The anti-cracking water reducing agent suitable for alkali-activated cement according to claim 1, characterized in that: The mass fraction of the alkali solution is 30-40%.
4. The anti-cracking water reducing agent suitable for alkali-activated cement according to claim 1, characterized in that: The sulfate includes at least one of sodium sulfate and potassium sulfate.
5. The anti-cracking water reducing agent suitable for alkali-activated cement according to claim 1, characterized in that: The mass fraction of the sulfate solution is 20-30%.
6. The anti-cracking water reducing agent suitable for alkali-activated cement according to any one of claims 1 to 5, characterized in that: The mass fraction of the formaldehyde solution is 40-55%.
7. Use of the anti-cracking water-reducing agent according to any one of claims 1 to 6 in alkali-activated cement-based concrete materials.
8. The use according to claim 7, characterized in that: The dosage of the anti-cracking water reducing agent is 1-3% of the alkali activated cement component.
Citation Information
Patent Citations
Low-cost modified naphthalene-based superplasticizer with high slump-keeping property and preparation method thereof
CN105801786A